INTEREST IN USING OVO: THE ROLE OF TRUST IN MEDIATING SECURITY AND PERCEIVED EASE OF USE - Casanova, Mercy; Nugroho, Arief Teguh (JURNAL ILMU MANAJEMEN, 2024)
This study discusses interest in using OVO: the role of trust in mediating security and perceived ease of use. Then, the purpose of this study is to determine (1) The effect of security on digital wallets (e-wallets) OVO on interest in using (2) The effect of security on digital wallets (e-wallets) OVO on trust in digital wallet applications (e-wallets) (3) The effect of trust in digital wallets (e-wallets) OVO on interest in using (4) The effect of perceived convenience on digital wallets (e-wallets) OVO on interest in using (5) The effect of security mediated by trust has a significant positive effect on interest in using OVO. The method used in this research is quantitative. The primary data sources used are questionnaires and journals. The sampling technique used was a proportional sampling technique, and sampling in this study was carried out by distributing questionnaires to a total of 100 respondents. The analysis technique used in this research is SmartPLS (Partial et al.) 3.0 with version 3.2.9. The results of this study indicate that (1) the security variable is proven to have no significant effect on interest in using (2) Security is proven to have an influence on trust (3) Trust is proven to have an influence on interest in using (4) Perception of convenience is proven to have no significant effect on interest in using (5) Trust can mediate security on interest in using OVO e-wallets.